Biologically active metabolite(s) from haemolymph of red-headed centipede Scolopendra subspinipes possess broad spectrum antibacterial activity - Ali, Salwa Mansur (AMB Express, 2019)
The discovery of novel antimicrobials from animal species under pollution is an area untapped. Chinese red-headed centipede is one of the hardiest arthropod species commonly known for its therapeutic value in traditional Chinese medicine. Here we determined the antibacterial activity of haemolymph and tissue extracts of red-headed centipede, Scolopendra subspinipes against a panel of Gram-positive and Gram-negative bacteria. Lysates exhibited potent antibacterial activities against a broad range of bacteria tested. Chemical characterization of biologically active molecules was determined via liquid chromatography mass spectrometric analysis. From crude haemolymph extract, 12 compounds were identified including: (1) l-Homotyrosine, (2) 8-Acetoxy-4-acoren-3-one, (3) N-Undecylbenzenesulfonic acid, (4) 2-Dodecylbenzenesulfonic acid, (5) 3H-1,2-Dithiole-3-thione, (6) Acetylenedicarboxylate, (7) Albuterol, (8) Tetradecylamine, (9) Curcumenol, (10) 3-Butylidene-7-hydroxyphthalide, (11) Oleoyl Ethanolamide and (12) Docosanedioic acid. Antimicrobial activities of the identified compounds were reported against Gram-positive and Gram-negative bacteria, fungi, viruses and parasites, that possibly explain centipede’s survival in harsh and polluted environments. Further research in characterization, molecular mechanism of action and in vivo testing of active molecules is needed for the development of novel antibacterials.